Generalized pustular psoriasis following allogeneic stem cell transplantation. (4th December 2014) - George, L.; Mathews, V.; George, B.; Thomas, M.; Pulimood, S. A.
Summary Development of psoriasis following allogeneic stem cell transplantation (SCT) is rare, and has been described once previously, following SCT from a sibling donor with psoriasis. This condition should be differentiated from psoriasiform graft‐versus‐host disease (GvHD) by histopathology. We describe a 9‐year‐old boy who developed generalized pustular psoriasis 2 months after allogeneic SCT from an HLA‐identical sibling donor with no history of psoriasis. Diagnosis was confirmed by clinical features and multiple skin biopsies, which helped to exclude GvHD. The skin lesions responded well to treatment with acitretin. Psoriasis should be considered in the differential diagnosis of skin rash following SCT.